1992
DOI: 10.1242/jcs.103.1.245
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of the fiber cell intrinsic membrane proteins MP20 and connexin46 in the bovine lens

Abstract: MP20 is an intrinsic membrane protein previously identified in mammalian lens fiber cells. To identify a possible role for this protein in the lens, the distribution of MP20 and connexin46 has now been examined. Western immunoblotting with an anti-peptide antibody generated to the C-terminal 8 amino acids of MP20 confirmed the presence of this protein in the lens of several different mammalian species. A monoclonal antibody 5H1 was prepared that, in Western blots of bovine lesn membranes, recognized the same c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Gap junctions, also known as membrane channels, are made of three kinds of connexins, Cx43, Cx46, and Cx50 [9,185]. Cx46 is found mainly in the cortex and the outer nuclear layers, and Cx50 is found mainly in the nuclear core [186][187][188]. Six connexins form a connexon, and two connexons from neighboring cells form a gap junction.…”
Section: Interaction Of α-Crystallin With the Lens Integral Membrane Proteinsmentioning
confidence: 99%
“…Gap junctions, also known as membrane channels, are made of three kinds of connexins, Cx43, Cx46, and Cx50 [9,185]. Cx46 is found mainly in the cortex and the outer nuclear layers, and Cx50 is found mainly in the nuclear core [186][187][188]. Six connexins form a connexon, and two connexons from neighboring cells form a gap junction.…”
Section: Interaction Of α-Crystallin With the Lens Integral Membrane Proteinsmentioning
confidence: 99%
“…In addition, these experiments indicate that the change in the electrophoretic mobility primarily represents the phosphorylation of the proteins. Both Cx46 and Cx50 are known to be phosphoproteins [ 6 , 19 , 20 , 21 , 22 , 23 , 24 ]. Previous immunoblotting experiments using ovine, bovine, and rat samples have shown that alkaline phosphatase treatment modifies the electrophoretic mobility of immunoreactive Cx46 and Cx50 [ 6 , 19 , 20 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both Cx46 and Cx50 are known to be phosphoproteins [ 6 , 19 , 20 , 21 , 22 , 23 , 24 ]. Previous immunoblotting experiments using ovine, bovine, and rat samples have shown that alkaline phosphatase treatment modifies the electrophoretic mobility of immunoreactive Cx46 and Cx50 [ 6 , 19 , 20 , 21 , 22 ]. In rat lenses, Cx46 is mainly detected as two bands of 46 and 54 kDa; both forms are present at embryonic ages, but the slower (phosphorylated) form predominates in young adults [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…All of the lens connexins are phosphoproteins ( Musil et al, 1990 ; TenBroek et al, 1992 ; Jiang et al, 1993 ; Berthoud et al, 1994 ; Gupta et al, 1994 ; Jiang et al, 1994 ; TenBroek et al, 1994 ; Berthoud et al, 1997 ; Shearer et al, 2008 ; Wang and Schey, 2009 ; Wang et al, 2013 ; Myers et al, 2018 ). Changes in phosphorylation of connexins (at different sites) can affect many aspects of the connexin life-cycle and channel function ( Sáez et al, 2003 ; Solan and Lampe, 2005 ; Solan and Lampe, 2014 ; Leybaert et al, 2017 ).…”
Section: Alterations Of Kinases and Phosphatases May Affect Connexin ...mentioning
confidence: 99%